Cannabis use and first-episode psychosis: relationship with manic and psychotic symptoms, and with age at presentation. Issue 3 (24th May 2013) - Stone, J. M.; Fisher, H. L.; Major, B.; Chisholm, B.; Woolley, J.; Lawrence, J.; Rahaman, N.; Joyce, J.; Hinton, M.; Johnson, S.; Young, A. H.
Abstract : Background: Cannabis use has been reported to be associated with an earlier onset of symptoms in patients with first-episode psychosis, and a worse outcome in those who continue to take cannabis. In general, studies have concentrated on symptoms of psychosis rather than mania. In this study, using a longitudinal design in a large naturalistic cohort of patients with first-episode psychosis, we investigated the relationship between cannabis use, age of presentation to services, daily functioning, and positive, negative and manic symptoms. Method: Clinical data on 502 patients with first-episode psychosis were collected using the MiData audit database from seven London-based Early Intervention in psychosis teams. Individuals were assessed at two time points – at entry to the service and after 1 year. On each occasion, the Positive and Negative Syndrome Scale, Young Mania Rating Scale and Global Assessment of Functioning Scale disability subscale were rated. At both time points, the use of cannabis and other drugs of abuse in the 6 months preceding each assessment was recorded. Results: Level of cannabis use was associated with a younger age at presentation, and manic symptoms and conceptual disorganization, but not with delusions, hallucinations, negative symptoms or daily functioning. Cannabis users who reduced or stopped their use following contact with services had the greatest improvement in symptoms at 1 year compared with continued users and non-users. Continued users remained more symptomatic than non-users at follow-up. Conclusions: Effective interventions for reducing cannabis use may yield significant health benefits for patients with first-episode psychosis.